Size fractionated NET‐Seq reveals a conserved architecture of transcription units around yeast genes - Xi, Shidong; Nguyen, Tania; Murray, Struan; Lorenz, Phil; Mellor, Jane (Yeast (Chichester, England), 2024)
Genomes from yeast to humans are subject to pervasive transcription. A single round of pervasive transcription is sufficient to alter local chromatin conformation, nucleosome dynamics and gene expression, but is hard to distinguish from background signals. Size fractionated native elongating transcript sequencing (sfNET‐Seq) was developed to precisely map nascent transcripts independent of expression levels. RNAPII‐associated nascent transcripts are fractionation into different size ranges before library construction. When anchored to the transcription start sites (TSS) of annotated genes, the combined pattern of the output metagenes gives the expected reference pattern. Bioinformatic pattern matching to the reference pattern identified 9542 transcription units in Saccharomyces cerevisiae, of which 47% are coding and 53% are noncoding. In total, 3113 (33%) are unannotated noncoding transcription units. Anchoring all transcription units to the TSS or polyadenylation site (PAS) of annotated genes reveals distinctive architectures of linked pairs of divergent transcripts approximately 200nt apart. The Reb1 transcription factor is enriched 30nt downstream of the PAS only when an upstream (TSS −60nt with respect to PAS) noncoding transcription unit co‐occurs with a downstream (TSS +150nt) coding transcription unit and acts to limit levels of upstream antisense transcripts. The potential for extensive transcriptional interference is evident from low abundance unannotated transcription units with variable TSS (median −240nt) initiating within a 500nt window upstream of, and transcribing over, the promoters of protein‐coding genes. This study confirms a highly interleaved yeast genome with different types of transcription units altering the chromatin landscape in distinctive ways, with the potential to exert extensive regulatory control. In this article, the authors describe high‐resolution mapping of the nascent yeast transcriptome using size fractionated NET‐Seq to resolve overlapping and lowly expressed transcription units, and reveal a distinct architecture of divergent coding and noncoding transcripts initiating approximately 200nts apart at the 5′ and 3′ end of genes. The Reb1 transcription factor binds 30nt downstream from the polyadenylation site of an upstream coding gene when linked to a downstream coding region and functions to limit upstream antisense transcription. Take‐away Size fractionated NET‐Seq maps nascent transcripts in Saccharomyces cerevisiae. sfNET‐Seq discovers transcription units independent of expression levels. sfNET‐Seq resolves overlapping and lowly expressed transcription units sfNET‐Seq reveals divergent promoters at the 5′ and 3′ ends of coding genes. Between tandem genes, Reb1 limits upstream antisense noncoding transcription.